Antecedents of philanthropic behavior of health care volunteers. Issue 4 (5th May 2015) - Alias, Siti Noormi; Ismail, Maimunah
Abstract : Purpose: – This paper aims to propose a conceptual model of philanthropic behavior of volunteers in the health care sector. Design/methodology/approach: – This study is based on an extensive review of past research on philanthropic behavior. To conduct the literature review, keywords such as philanthropy, philanthropic behavior, giving, donating, competencies, volunteering and social network in health care were identified. Findings: – From the literature reviewed, three groups of antecedents of philanthropic behavior among health care volunteers (HCVs) were identified, viz., individual factors, social factors and organizational factors. This paper proposes social network as a mediating variable in linking the three groups of antecedents with philanthropic behavior. The paper offers a number of propositions which explain the proposed model of philanthropic behavior of HCVs. Practical implications: – Further research is suggested to test and validate the framework to provide empirical evidence. Upon model validation, the paper could offer practical interventions for human resource development (HRD) managers to assist philanthropic-based organization toward developing and managing philanthropic behavior of HCVs. The paper highlights the importance of social network to promote individuals to engage in philanthropic actions. Originality/value: – The paper yields a new approach in theorizing philanthropic behavior among HCVs by integrating the theory of planned behavior, social identity approach and organizational support theory. The proposed social network as a mediator could provide new insights to the HRD practitioners on developing philanthropic behavior among HCVs subject to model validation. The research contributes to literature in philanthropy, HRD and community development.